<<Custodia legum civilitatis est indicium>>: Teoderico l’Amalo e la civiltà romana - Saitta, Biagio (Antigüedad y Cristianismo, 1990)
The ciuilitas of Thedoric not only can be appreciated in his desire to restore the ancient buildings and in the obvious refinement of the gifts he gave to Clodoveus and Gundobadus but also in his consideration towards the individual conscience of his subjects. His attitude in the religious ambitus is one of moderation and tolerance which converts him almost into a modern iluminated spirit. The cohesive force between the elements which compose his kingdom had to be based on the maintenance of the Law. This was his main preoccupation: with this in mind he gave orders to generals, praised the Senate, remonstrated all those who broke the laws, exalted those who worked in their keeping and punished the lawbreakers. The principal aim of his government was to maintain the ciuilitas. For this reason he favoured actions such as mixed marriages which helped the Goths enter into the romanitas and encouraged the implantation of the Roman civilization amongst the Gepids. That was the signiHcation he gave to the wars carried out in the Gallia in 508. This image of him was real and he was described in an inscription as custos libertatis et propagator Romani nominis.